MENGURAI KEKERASAN SIMBOLIK DIBALIK SERAGAM SEKOLAH DI SEKOLAH DASAR : (PANDANGAN PIERRE BOURDIEU TENTANG HABITUS DALAM PENDIDIKAN) - Mohulaingo, Rahmad; Pomalingo, Samsi; Halidu, Salma; Cuga, Candra (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze the existence of symbolic violence hidden behind the use of school uniforms at the elementary school level using Pierre Bourdieu's perspective, especially the concept of habitus in education. School uniforms, which are generally considered a tool to create equality and discipline, also turn out to be a medium of symbolic domination that reproduces social inequality. The approach to this research is a literature study with a descriptive-qualitative method, analyzing how school uniforms, as cultural symbols, contribute to the internalization of dominant values ​​by students. The results of the study indicate that school uniforms function as a device that strengthens the legitimacy of certain social norms, creating the illusion of equality among students. However, differences in socio-economic background remain visible through additional attributes, such as the quality of uniform materials, cleanliness, and accessories, which reflect the economic capital of students' families. This causes students from less dominant social groups to often feel inadequate or unequal, internalizing their subordinate positions. Educational institutions reinforce this symbolic violence through strict rules governing the use of uniforms, making symbolic domination seem natural and legitimate. This study emphasizes the importance of examining symbols in education, such as uniforms, which are often considered neutral but actually function as tools of domination. By understanding the symbolic violence behind school uniforms, it is hoped that a more equitable education system can be built, which not only creates formal uniformity but also embraces inclusivity and social justice.